2011
DOI: 10.1186/1472-6939-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues at the interface of clinical care and research practice in pediatric oncology: a narrative review of parents' and physicians' experiences

Abstract: BackgroundPediatric oncology has a strong research culture. Most pediatric oncologists are investigators, involved in clinical care as well as research. As a result, a remarkable proportion of children with cancer enrolls in a trial during treatment. This paper discusses the ethical consequences of the unprecedented integration of research and care in pediatric oncology from the perspective of parents and physicians.MethodologyAn empirical ethical approach, combining (1) a narrative review of (primarily) quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 62 publications
(78 reference statements)
4
91
0
1
Order By: Relevance
“…The difficulty some parents had in distinguishing clinical treatment from research reflects previous reports, [8][9][10][11] while the finding about parental reassurance and sense of control are in line with earlier work relating to consent by proxy. [7][8][9][10][11] Studies on lay understanding of the purpose of genetic sampling have also found a lack of concern about this. 14 15 Implications for the conduct of research We concur with the view that representative ethnic minority participation in trials is feasible if researchers take appropriate steps to facilitate this.…”
Section: Comparison With the Existing Literaturesupporting
confidence: 79%
See 1 more Smart Citation
“…The difficulty some parents had in distinguishing clinical treatment from research reflects previous reports, [8][9][10][11] while the finding about parental reassurance and sense of control are in line with earlier work relating to consent by proxy. [7][8][9][10][11] Studies on lay understanding of the purpose of genetic sampling have also found a lack of concern about this. 14 15 Implications for the conduct of research We concur with the view that representative ethnic minority participation in trials is feasible if researchers take appropriate steps to facilitate this.…”
Section: Comparison With the Existing Literaturesupporting
confidence: 79%
“…7 Significant elements include parents' poor comprehension of the trial process, 8 the parental emotional turmoil related to paediatric illness and confusion born of the blurring of ethical boundaries between clinical and research practice. [9][10][11] Parent study The current study is embedded within a randomised controlled trial (the parent study) of the genetic determinants of the efficacy of intermittent montelukast in preschool wheeze (PSW) and provides an opportunity to investigate the perspectives of the parents of trial participants. It was hypothesised that a genetically determined subgroup of patients (with higher urinary inflammatory mediators) would respond better to montelukast (have reduced unscheduled medical attendance) than their peers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…If you add to this some ‘bad apple’ stories of when the experience of healthcare professionals of research being unwieldy, impractical and unusable in the ’real world' of clinical practice along with ethical knots that may be tied20 there is a chunky barrier to overcome. It can be possible though—and there are several examples to demonstrate that it is practical.…”
Section: How Then To Move Forward?mentioning
confidence: 99%
“…The rationale for differentiating research and treatment in RCT conduct, as elaborated within an influential strain of predominantly bioethics literature, lies in the potential conflict between the treatment aim of enhancing the wellbeing of an individual patient and the research aim of producing generalizable knowledge to guide the care of future patients (Appelbaum, 2010;Belmont Report, 1979;Miller, 2004;Miller and Brody, 2003;Morreim, 2005;de Melo-Martín and Ho, 2008;de Vries et al, 2011). Healthcare professionals provide patients with individualized diagnostic procedures and treatments, guided by the patients' best interests.…”
Section: Introductionmentioning
confidence: 98%